Efektivitas Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) pada Pembelajaran Fisika Siswa Kelas VII SMP Negeri 5 Model Lubuklinggau - Nurul Latifah; Endang Lovisia (Journal on Education, 2024)
The physics learning outcomes off clas VII students are generally still low, this can be seen from the average scores which are still much below the students’ daily test scores. In order to overcome this, learning methods are needed that can increase enthusiasm for learning in a lesson and can increase the level of student learning outcomes. The TGT cooperatif learning model is one of the models that can increase motivation and improve student learning outcomes. The question that arises from this research is whether using the Team Games Tournament (TGT) learning paradigm provides a significant improvement in students’ physics learning outcomes. This research uses quasi-experiment and is quantitativ. A one group pretes-posttest design was used in this research. Ten multiple choice questions about the solar system were included in the pretest-posttest test used in the data collection method. The t-test is used inthe data analysis method.